Lean Six Sigma imperatives for casting quality improvement of automotive components: a case. (3rd November 2021) - Rathi, Rajeev; Singh, Mahipal
Lean Six Sigma (LSS) is a systematic operation management strategy aimed to improve the quality of products through the reduction of process variations and wastes. In the present case, an LSS strategy is implemented in the automotive components manufacturing industry to improve the casting quality and productivity. The main purpose of this research is to extract the various causes of the existence of casting defects and suggest corresponding remedies to pawn them. The result of the case study exhibits the increment in sigma level of the company from 1.90 to 3.30 and analogous escalation in an annual profit of 1.2 million. The outcomes of this study facilitate to industrial managers and practitioners for adopting the same strategy to resolve their complex problems and to achieve business excellence.